PUBLIC SPEAKING EFFECTIVITY IN COMMUNICATING BEST FEATURES AND BENEFITS OF MERCURE HOTEL - Sitti Humaerah. P; Indrawaty Asfah; Seny Luhriyani (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
This study describes how effective public speaking techniques help communicate the unique features and benefits of Mercure Hotel in Makassar. Public speaking is crucial in the hospitality industry for influencing customer perceptions and enhancing engagement. The research utilizes qualitative methods through questionnaires, distributed both online and face-to-face, to capture the perspectives of hotel guests and staff. The findings show that verbal and nonverbal communication significantly improve customer satisfaction and loyalty. Verbal communication helps convey clear messages, while nonverbal elements like eye contact and body language strengthen emotional connections. This study suggests that training hotel staff in public speaking can enhance their ability to effectively engage with customers and promote the hotel's offerings, thereby increasing guest loyalty and brand reputation.